2022
DOI: 10.1371/journal.pone.0263791
|View full text |Cite|
|
Sign up to set email alerts
|

Evidence that dog ownership protects against the onset of disability in an older community-dwelling Japanese population

Abstract: Objectives This study examined the association between dog and cat ownership, the onset of disability and all-cause mortality in an older population. Dog and cat owners take more regular exercise and have closer social relationships than non-owners. We further assess the beneficial effects of these moderating variables on the onset of disability and mortality. Methods Dog and cat ownership data were collected from 11233 community-dwelling adults age 65 years and older. These data were matched with data about… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 31 publications
2
12
0
Order By: Relevance
“…Missing values (n): education level (3), financial difficulties (1), living alone (8), home type (6), home location (22), home characteristics (5), comorbidities (13), BADL impairment (6), IADL impairment (36), walking difficulty (18), fear of falling (4), memory difficulties (12), depressive symptoms (3), anxiety symptoms (11), feelings of loneliness (4), usual social support (235), emotional support (15), previous participation in group activities (35), having a dog (4), having a cat (4), unfamiliarity with communication technology (30) and death of a partner in the past year (23).…”
Section: Resultsmentioning
confidence: 99%
“…Missing values (n): education level (3), financial difficulties (1), living alone (8), home type (6), home location (22), home characteristics (5), comorbidities (13), BADL impairment (6), IADL impairment (36), walking difficulty (18), fear of falling (4), memory difficulties (12), depressive symptoms (3), anxiety symptoms (11), feelings of loneliness (4), usual social support (235), emotional support (15), previous participation in group activities (35), having a dog (4), having a cat (4), unfamiliarity with communication technology (30) and death of a partner in the past year (23).…”
Section: Resultsmentioning
confidence: 99%
“…Our previous longitudinal studies revealed that the odds ratios for incidence of frailty in community-dwelling adults aged 65 years or older were 0.87 (95% confidence interval [CI]: 0.69-1.09) for current dog or cat owners and 0.84 (0.71-0.98) for past owners, after controlling for important confounders, compared with "never" owners [16,17]. We also recently reported that older adults who currently owned a dog had a lower odds ratio of onset of disability (OR = 0.54, 95% CI: 0.37-0.79) compared to a reference group that had never owned a dog [18].…”
Section: Introductionmentioning
confidence: 83%
“…This study defined pets as dog, cat or other animals, however detailed information for other animals is not clear. Previous studies have reported superior protective effects against adverse health outcomes for dog ownership compared to cat ownership [16][17][18]. Further research is needed to examine the medical and long-term care costs among dog owners compared to cat owners.…”
Section: Plos Onementioning
confidence: 97%
See 1 more Smart Citation
“…These complex differences in outcomes among dog and cat owners may have resulted in different needs in caring for different species. For instance, most dogs – but not cats – require daily walking, meaning dog ownership may contribute to maintaining the physical health of older adults (Taniguchi et al, 2022). Given that cats are generally seen as being easier than dogs to take care of, an increasing number of older Japanese pet owners now prefer cats to dogs.…”
mentioning
confidence: 99%